Hormonal and Histological Study of the Effect of Co Enzyme Q10 on Male Reproductive System of Wister Rats Exposed to Cadmium Chloride - Muntasser Alawi Awad (Journal of Madenat Alelem University College, 2022)
The aim of this study was to investigate  at the effect of co enzyme CO 10, which acts as an antioxidant, on the male reproductive system of rats treated by cadmium chloride. (40) male rats were divided as follows: The control group received just drinking water, the T1 group received Q10 (10 mg/kg) for 60 days, the T2 group received cadmium chloride (25 mg/kg) for 60 days and the T3 group received cadmium chloride (25 mg/kg)+ Q10 (10 mg/kg) for 60 days. The results showed there were a significant increase (p≤0.05) in testosterone hormone level in T1 group compared with other groups (C,T2,T3). While there were a significant decrease in T2 group compared with control group. ICSH increased significantly in the T1 group as compared to the T2 group, but there were no significant differences between the other groups. GnRH levels were significantly increased in the T1 group compared to the other groups, but there were no significant differences between the C,T2, and T3 groups. Testicular sections from rats in the T2 group that were administered cadmium chloride revealed impairment in the function of the testes, epididymis, and vas deference, as well as a reduction in the number of sertoli cells .Testicular sections of rats in the T3 group that were administered cadmium chloride and treated with Q10 revealed full spermatogenesis with prominent sertoli cells. The epididymial duct has normal and high epithelial cells and stereo cilia, with a large amount of sperms in its lumen; the vas deference has high columnar epithelial cells, long and extended stereo cilia, and normal smooth muscle fiber. The present study shows that the antioxidant properties of CoQ10 the basis of the ameliorative role of male reproductive system. Evidence reveals that CoQ10 mainly improves male hormones and testicular function and protects it from oxidative damage by cadmium chloride.